Aplicación Móvil para la Organización Juancho Correlón - Arce Gómez, Camilo Andrés (Ingenierias, 2017)
This document presents the development of the application Juancho Correlón, made by the students of the University San Buenaventura-Cali. Within this will be discussed about the process completed for the completion of the application.